Resilience and acculturation among unaccompanied refugee minors. (January 2018) - Keles, Serap; Friborg, Oddgeir; Idsøe, Thormod; Sirin, Selcuk; Oppedal, Brit
The present study was designed to understand differences between unaccompanied refugees who retained or achieved good mental health ( healthy or resilient ) and those who maintained or developed poor mental health ( clinical and vulnerable ). Using person-based analyses, the role of pre-migration traumatic exposure and acculturation-related factors in long-term trajectories of psychological adjustment among unaccompanied refugees was explored. This study included three waves of data collection in a population-based sample. The participants were 918 unaccompanied refugees who had received asylum and residence status in Norway. The pattern of change in depression symptoms over time was used to characterize subgroups displaying resilient, vulnerable, clinical or healthy trajectories. Results indicated that the extent of post-migration acculturation hassles and heritage culture competence, as well as pre-migration traumatic events and gender, distinguished the refugee groups in terms of mental health trajectories. The implications for clinical practice and immigration policy are discussed.